The Metamorphic Changes During Post Embryonic Development and Ultrastructure of Antennae in Red Eye Bug, Leptocoris augur (Hemiptera: Rhopalidae) - Barsagade D.D.; Badwaik V.J. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
The red eye bug Leptocoris auguar is economically important pest as it damage soapberry (rittha) plant, Sapindus saponaria, other vegetables and fruit plants. The post embryonic development of the soapberry bug, L. augur passes through five nymphal instars and adults (male, female). No sexual metamorphic dimorphism found in the adults except their body length. The eggs are rough barreled, bean shaped and red coloured. The bug has four segmented filliform type of antennae, divided into three parts, scape, pedicel and two segmented flagellum. The surface ultrastructural study of antenna showing the presence of three different types of sensilla as sensilla trichoidea (ST-I and ST-II), sensilla trichoidea curvata (STC) and sensilla basiconica (SB). The button like structure present between adjecent segment containing hexagonal and pentagonal plates.